2018
DOI: 10.1080/14786419.2018.1425848
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant potential and in vivo effects of Schinus terebinthifolia Raddi leaf extract in diabetic rats and determination of chemical composition by HPLC-ESI-MS/MS

Abstract: The present study investigated the in vitro and in vivo antioxidant potential and phytochemical composition of Schinus terebinthifolia, which is widely used in folk medicine for various therapeutic purposes. The in vitro analyses indicated that the hydroethanolic extract (HE) had 312.50 ± 0.50 mg GAE/g of total phenols. It also presented anti-DPPH• and anti-ABTS• activity, reduced phosphomolybden and metal ions and blocked the bleaching of β-carotene. The HE at concentrations of 3.0 and 2.0 μg/mL had TRAP valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Decne ( Srinuanchai et al., 2021 ), Aegle marmelos (L.) Corrêa ( Sharma et al., 2007 ), B. alba L. ( Bamidele et al., 2014 ; Ahmed, 2022 ), Glinus oppositifolius (L.) Aug.DC ( Behera et al., 2010 ), Amaranthus lividus Linn. ( Sangameswaran and Jayakar, 2008 ), Dregea volubilis Benth ( Thuy et al., 2021 ; Natarajan and Dhas, 2013 ; Natarajan et al., 2020 ), S. terebinthifolius Raddi ( da Rocha et al., 2019 ; Iwanaga et al., 2019 ), Tiliacora triandra (Colebr.) Diels ( Katisart and Rattana, 2017 ; Makinde et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Decne ( Srinuanchai et al., 2021 ), Aegle marmelos (L.) Corrêa ( Sharma et al., 2007 ), B. alba L. ( Bamidele et al., 2014 ; Ahmed, 2022 ), Glinus oppositifolius (L.) Aug.DC ( Behera et al., 2010 ), Amaranthus lividus Linn. ( Sangameswaran and Jayakar, 2008 ), Dregea volubilis Benth ( Thuy et al., 2021 ; Natarajan and Dhas, 2013 ; Natarajan et al., 2020 ), S. terebinthifolius Raddi ( da Rocha et al., 2019 ; Iwanaga et al., 2019 ), Tiliacora triandra (Colebr.) Diels ( Katisart and Rattana, 2017 ; Makinde et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are more than 13 million diabetics aged 20 to 79 years and 88,300 children and adolescents in Brazil. 1,2 In addition the classic symptoms of chronic hyperglycemia, which leads to an imbalance of antioxidants, [3][4][5] diabetics suffer from complications in the gastrointestinal tract. 6 Dysphagia, abdominal pain, diarrhea, and constipation are symptoms that affect the quality of life of diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…The bark and fruits are used to treat urinary and uterine affections, bleeding and diarrhea, and rheumatic and respiratory diseases. Antioxidant (Bendaoud et al, 2010 ; Feriani et al, 2021 ; Kim et al, 2021 ; Oliveira et al, 2020b ), antibacterial (D'Sousa' Costa et al, 2015 ; Linden et al, 2020 ; Salem et al, 2018 ), antifungal (Giordani et al, 2022 ), antidiabetic (Dos Santos da Rocha et al 2019 ; Iwanaga et al, 2019 ), and other bioactivities have been reported. Anti-inflammatory properties, for example, have been linked to the composition of polyphenols, as well as monoterpenes and sesquiterpenes in the essential oil (Feriani et al, 2020 ; Formagio et al, 2011 ; Kim et al, 2021 ; Marangoni et al, 2022 ; Rosas et al, 2015 ; Yueqin et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%